2019
DOI: 10.3390/su11133540
|View full text |Cite
|
Sign up to set email alerts
|

Buildingmass and Energy Demand in Conventional Housing Typologies of the Mediterranean City

Abstract: The causal relation among building typology and building energy demand is a complex balance of climate, morphology, technology and use. The assessment of the relation between mass of building elements and energy demand in different housing typologies is the main goal of this study. A novel indicator, namely the Buildingmass, is introduced and tested in the Mediterranean climate region. Explorations on nine conventional housing typologies in Barcelona and Rome are carried out. Buildingmass evaluation is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Several researchers have recently applied housing indicators in order to achieve or enhance sustainability [16][17][18][19][20][21][22][23]; some of these investigations refer to social housing [17,18,21,22]. Among the indicators that were analyzed are those referring to household vulnerability; these studies found that social housing tends to be inhabited by people with below-average incomes [18,21] who are vulnerable to energy poverty.…”
Section: Background and Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have recently applied housing indicators in order to achieve or enhance sustainability [16][17][18][19][20][21][22][23]; some of these investigations refer to social housing [17,18,21,22]. Among the indicators that were analyzed are those referring to household vulnerability; these studies found that social housing tends to be inhabited by people with below-average incomes [18,21] who are vulnerable to energy poverty.…”
Section: Background and Research Objectivesmentioning
confidence: 99%
“…In this sense, Monzón et al [17] developed a system of indicators to detect multifamily dwellings that have weak energy, acoustic, and accessibility performance. Similarly, Morganti et al [20] proposed an indicator called building mass, which may contribute to the reduction of energy demand. Other works have proposed social and economic indicators that can help to predict the origin of mortgages as well as housing prices [16].…”
Section: Background and Research Objectivesmentioning
confidence: 99%